Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2001
DOI: 10.1111/j.1740-8261.2001.tb00987.x
|View full text |Cite
|
Sign up to set email alerts
|

REGIONAL BRAIN PERFUSION IN 10 NORMAL DOGS MEASURED USING TECHNETIUM‐99m ETHYL CYSTEINATE DIMER SPECT

Abstract: Single photon emission computed tomography (SPECT) of the brain using perfusion tracers allows estimation of regional brain perfusion. This allows in vivo examination of brain function in the setting of neuropsychologic and pathophysiologic changes. However functional imaging data on brain perfusion in dogs are limited. Hence, the aim of this study was to determine the scintigraphic regional perfusion pattern of the normal canine brain. Ten healthy shepherd type dogs were injected with 925 MBq Technetium-99m e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 10 publications
1
30
2
Order By: Relevance
“…Thus, the age and sex of our subjects were biased towards a young age and the female gender. A previous study of normal dogs that analyzed regional brain perfusion using technetium-99 m ethyl cysteinate dimer and single photon emission computed tomography (SPECT) found that in normal shepherd-mix dogs, age (1 to 9 years) and gender did not influence the perfusion pattern in 7 ROIs, frontal cerebral, temporal cerebral, parietal cerebral, occipital cerebral, cerebellar, thalamic and striatal areas [8]. Cerebral glucose metabolism and cerebral blood flow correlate positively [14] thus, it is assumed that the effect of age and sex are not critical.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the age and sex of our subjects were biased towards a young age and the female gender. A previous study of normal dogs that analyzed regional brain perfusion using technetium-99 m ethyl cysteinate dimer and single photon emission computed tomography (SPECT) found that in normal shepherd-mix dogs, age (1 to 9 years) and gender did not influence the perfusion pattern in 7 ROIs, frontal cerebral, temporal cerebral, parietal cerebral, occipital cerebral, cerebellar, thalamic and striatal areas [8]. Cerebral glucose metabolism and cerebral blood flow correlate positively [14] thus, it is assumed that the effect of age and sex are not critical.…”
Section: Discussionmentioning
confidence: 99%
“…In the feline brain the cerebellum is the region with the lowest perfusion index, whereas, in dogs, the cerebellar tracer uptake is higher than in the cortical regions, but lower than in the subcortical region. 5 An age-related decrease in the ECD perfusion pattern and an increased left-right asymmetry was observed in several brain regions in humans. 6,15 Also, in dogs, a decreased perfusion in the frontotemporal cortex and in the subcortical region, together with a significant leftright difference in the parietal cortex, was reported in a group of 'aged' dogs (older than 96 months) when compared with a reference group (aged between 12 and 84 months).…”
Section: Discussionmentioning
confidence: 99%
“…Similar to dogs and humans, the uptake of 99m Tc-ECD also varies significantly between brain regions in the feline brain. 5,6,15 The highest uptake occurs in the subcortical structures like the amygdala, hippocampus, basal ganglia and thalamus, and in the cingulate gyrus (Table 2), which reflects the relative dominance of these structures in feline behaviour. ECD is a 99m Tc-labelled lipophilic tracer used for SPECT imaging of rCBF.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations